THE IMPACT OF THE INSTITUTIONAL ENVIRONMENT ON THE ECONOMIC DEVELOPMENT - Jankauskas, Vidmantas; Šeputienė, Janina (Ekonomika, 2009)
Economic literature recognizes three “deep determinants” of economic development: institutions, geography and openness to trade. Discussion in the literature focuses on what part of the income per capita variation can be explained by institutions, geography and openness to trade. The empirical results can’t offer a clear answer, but there is a broader agreement in the literature that institutions play a more important role than geography and openness to trade. What is unclear whether the institutions also can explain variation in per capita income across countries, in which institutional environment is to some degree similar.. This article aims to explore and quantify the relationship of the income level with institutional environment, geography and openness to trade across countries, grouped according their institutional environment quality. The results reveal that extent to which the variation in GDP per capita can be associated with the quality of institutional environment differs a lot between good and bad institutional environment samples. The results in good institutional environment sample come in line with series of studies in which the strong and positive link between various measures of institutions and economic development was established and support primacy of institutions over openness to trade and geography. I In bad institutional environment sample, on the contrary,no evidence was found that institutions mean a lot in respect of differences in GDP per capita. These results should not be interpreted so as to mean that institutional environment is not important, rather the degree of “badness” makes no difference.